Children in Digital Age - Kata Zsófia Prém, Laura Kovács-Berényi; Halász, Csenge (2025)
The volume Children in Digital Age examines how children’s rights are affected by the rapid expansion of digital technologies, online platforms and social media. Its central question is how existing legal systems can respond to phenomena that increasingly shape children’s everyday lives, including cyberbullying, harmful online content, sharenting, targeted advertising, misinformation, excessive screen use, and the long-term consequences of children’s digital footprints.The book combines psychological, international, European and comparative legal perspectives. The psychological chapter shows that online platforms may support learning, communication and social development, but they may also create risks for children’s mental health, sleep, self-esteem and emotional well-being. The international and European chapters place these issues within the broader framework of children’s rights protection, with particular attention to the UN Convention on the Rights of the Child, European legal standards, EU regulatory instruments and safer internet initiatives.The comparative part of the volume focuses on Croatia, the Czech Republic, Hungary, Poland, Romania, Serbia, Slovakia and Slovenia. The country reports analyse the protection of children’s rights online through national constitutional, civil, criminal, media, data protection and child-protection rules. They show that, although the examined states rely on similar international and European foundations, their regulatory techniques, institutional frameworks and case law differ considerably.A recurring finding of the volume is that many legal systems still address digital-age harms through traditional legal categories. This is particularly visible in relation to privacy, freedom of expression, access to information, protection from abuse, and the right to education. The book therefore highlights the need for a more coherent child-centred approach, in which legal regulation, institutional practice, platform responsibility, parental awareness and digital education reinforce one another.The volume does not present the digital environment solely as a source of danger. Rather, it argues that children should be protected from online harms without being excluded from the benefits of digital participation. The protection of children in the digital age requires a careful balance between safety, autonomy, participation and responsibility. This balance is the central challenge addressed by the studies collected in this book.